Strongyloides stercoralis seropositivity is not associated with increased symptoms in a remote Aboriginal community. Issue 8 (22nd August 2021) - Hansen, Martin; Bowden, Emily; Currie, Bart J.; Ward, Linda; Andrews, Ross M.; Dhurrkay, Roslyn Gundjirryirr; Gurruwiwi, George Garambaka; Kearns, Therese
Abstract: Background: Strongyloides stercoralis is a soil‐transmitted helminth, endemic in remote Aboriginal and Torres Strait Islander communities in northern Australia with estimates of prevalences up to 60%. Hyperinfection in the setting of immunosuppression is a rare, but well recognised cause of significant morbidity and mortality. However, the morbidity associated with chronic uncomplicated infection is less well characterised. Aims: To measure the prevalence of symptoms potentially attributable to S. stercoralis infection and their association with seropositivity. Methods: This retrospective matched case‐control study reviewed records of primary healthcare presentations for symptoms in the 12 months before and after an ivermectin mass drug administration (MDA) in a remote Aboriginal community. Results: One hundred and seventy‐five S. stercoralis seropositive cases were matched with 175 seronegative controls. The most frequently reported symptom overall in the 12 months prior to the MDA was cough followed by abdominal pain, weight loss/malnutrition, diarrhoea and pruritis. Seropositive cases were not more likely than matched controls to have symptoms typically attributed to strongyloidiasis. In the seropositive cohort, we found no difference in symptoms in the 12 months before and after an ivermectin MDA despite a reduction in seroprevalence. Conclusion: We found no evidence to suggest that S. stercoralis seropositivity was associated with increased symptoms when compared to matched seronegative controls. Treatment with ivermectin did not reduce symptoms in seropositive cases. Without evidence to support that population‐based screening or treatment programmes reduce symptoms, the emphasis must remain on identifying and managing those few individuals with immunosuppression that predisposes them to potentially life‐threatening hyperinfection.